Dual–phase Spinel MnCo2O4 Nanocrystals with Nitrogen-doped Reduced Graphene Oxide as Potential Catalyst for Hybrid Na–Air Batteries. (1st August 2017) - Kang, Yao; Zou, Da; Zhang, Jianyong; Liang, Feng; Hayashi, Katsuro; Wang, He; Xue, Dongfeng; Chen, Kunfeng; Adair, Keegan R.; Sun, Xueliang
Graphical abstract: Highlights: dp -MnCo2 O4 /N-rGO bifunctional catalyst was used in hybrid Na-air battery. Battery exhibited comparable ORR and superior OER performance compared to Pt/C. A low overpotential of 0.39 V was obtained using dp -MnCo2 O4 /N-rGO catalyst. The fabricated hybrid Na-air batteries exhibit stable discharge performance. Abstract: The electrochemical performance of Na–air batteries have a significant dependence on the type of electrocatalyst used for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Herein, a dual-phase spinel MnCo2 O4 with nitrogen-doped reduced graphene oxide hybrid ( dp -MnCo2 O4 /N-rGO) employed in a hybrid Na-air battery system was demonstrated simultaneous electrocatalytic characteristic toward both ORR and OER, which showed comparable ORR and superior OER catalytic performance over commercial Pt/C. The fabricated dual-phase cobalt manganese spinel nanoparticles, the introduced dopants (nitrogen atoms), and the electrical and chemical coupling between the oxide nanoparticles and nanocarbon backbones significantly contribute to the high catalytic performance of dp -MnCo2 O4 /N-rGO. The proposed catalyst exhibited a slightly higher discharge voltage of 2.75 V and lower charge voltage of 3.14 V compared to that of a commercial Pt/C (2.73 and 3.35 V, respectively). The hybrid battery showed a low overpotential of 0.39 V and improved round-trip energy efficiency. The battery exhibited excellent discharge stability and no significant degradation was observed during the 25 cycles due to the moderate particle size of dp -MnCo2 O4 and large active N-doped surface area. Therefore, dp -MnCo2 O4 /N-rGO could be a promising bifunctional catalyst for enhancing the electrochemical performance of hybrid Na-air batteries.